Adult Sized Fibreoptic Bronchoscope Aided Nasal Intubation In A Child with Left Sided Temporomandibular Joint Ankylosis - Ghimire, Ashish; Bhattarai, B; Subedi, A; Koirala, S (Health Renaissance, 2015)
In temporomandibular joint (TMJ) ankylosis, direct laryngoscopy and intubation are not feasible. The scenario becomes more challenging in paediatric patients. The best technique would be fibreoptic bronchoscope (FOB) aided nasal intubation. We report successful nasal intubation with the aid of orally placed adult sized fibreoptic bronchoscope in a child with a limited mouth opening. A 6-yr-old child was brought with history of inability to open the mouth. Diagnosis of left sided TMJ ankylosis was made and interpositional arthoplasty was planned. Airway examination revealed interincisor gap of 4.6 mm. Due to tooth decay, a maximum mouth opening of 5.2 mm was observed on the left side. The airway was successfully secured through the nasal route aided by the adult sized bronchoscope inserted orally through the gap between the eroded upper and the lower teeth. Adult sized fibreoptic bronchoscope may be useful in aiding nasal intubation in pediatric patients if the mouth opening permits its introduction orally. DOI: http://dx.doi.org/10.3126/hren.v12i1.11986 Health Renaissance 2014;12(1):49-51